Exploring the Enigma of Particle Dynamics and Plasma Lensing Using Einstein–Euler–Heisenberg Black Hole Geometry - Allah Ditta; Raja Sikander Mehmood; Muhammad Fiaz; Bismillah Bibi; Sana Deen; Rimsha Jaffar; Asif Mahmood (Universe)
The unified Einstein–Euler–Heisenberg theory is utilized to investigate the particle motion and weak gravitational lensing characteristics of black holes. This black hole solution is developed using spherically symmetric possessing electric and magnetic charges. Quantum electrodynamics corrections reveal a screening effect for BH electric charges and paramagnetic impacts on magnetic charges. We analyzed the motion of massive as well as massless particles by studying their effective potential, event horizon, photon orbit and inner circular orbit. It was demonstrated that magnetic and electric fields of spherically symmetric black holes have significant impact. Then, we also delve to study the weak gravitational lensing phenomenon. A comprehensive approach was employed to investigate this phenomenon and explore the angle of deflection of light rays near magnetically and electrically charged black holes.